1998
DOI: 10.1007/s002679900117
|View full text |Cite
|
Sign up to set email alerts
|

Fish Community Structure as a Measure of Degradation and Rehabilitation of Riparian Systems in an Agricultural Drainage Basin

Abstract: / Assessing the health of ecological components of agroecosystems may be accomplished by examining changes in the drainage basin, which serves as an integrator of the agroecosystem landscape. In this study we examined fish communities in terms of an array of indicators of structure and related these to changes in riparian vegetation and agricultural practice. Evidence suggests management practices designed to foster healthier environments by, for example, reestablishing riparian vegetation were associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 44 publications
4
54
0
3
Order By: Relevance
“…Furthermore, it was seen that fish species diversity is high in undisturbed water courses with riparian vegetation cover, because they present a greater availability of habitats, low oscillation of environmental conditions (Wichert & Rapport, 1998;Stauffer et al, 2000;Vondracek et al, 2005;Gomiero & Braga, 2006) and availability of fish food, such as aquatic insects (Winemiller et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was seen that fish species diversity is high in undisturbed water courses with riparian vegetation cover, because they present a greater availability of habitats, low oscillation of environmental conditions (Wichert & Rapport, 1998;Stauffer et al, 2000;Vondracek et al, 2005;Gomiero & Braga, 2006) and availability of fish food, such as aquatic insects (Winemiller et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation in these areas is very heterogeneous, and riparian vegetation is one example of this variation, showing phytophysiognomies ranging from grassland to closed canopy (Ratter et al, 1997;Ribeiro & Walter, 1998). Considering the strong predictive power of riparian vegetation in structuring stream fish communities (Wichert & Rapport, 1998;Growns et al, 2003), it is plausible that the spatial distribution of fish species can be affected by alterations in the longitudinal variation of riparian vegetation structure in Cerrado streams.…”
Section: Introductionmentioning
confidence: 99%
“…In streams of Wisconsin (Richards & Host, 1994) and Michigan (Roth et al, 1996) the inverse correlation was significant and strong, up to r = -0.70. Similarly, Wichert and Rapport (1998) found that fish communities significantly declined in streams in Southern Ontario as agriculture intensified. For streams in Illinois, Fitzpatrick, Scudder, Lenz, and Sullivan (2001) reported that IBI values tend to be low when agriculture cover is >10 % in the stream buffer zone (r = -0.76).…”
Section: Discussionmentioning
confidence: 99%